Physiologic effects of furosemide in combination with water restriction when administered at 4 and 24 hours prior to high‐intensity treadmill training. Issue 6 (1st June 2020) - Knych, Heather K.; Wilson, W. David; Vale, Alina; Kass, Philip H.; Steffey, Eugene P.; Jones, James H.; Arthur, Rick M.
Abstract: Although controversial, due to its reported effectiveness in attenuating bleeding associated with exercise‐induced pulmonary hemorrhage (EIPH), furosemide is currently a permitted race day medication in most North American racing jurisdictions. The objective of this study was to assess the efficacy of furosemide in reducing the presence and severity of EIPH when administered 24 hr prior to strenuous treadmill exercise. Eight exercised Thoroughbred horses received saline or 250 mg of furosemide either 4 or 24 hr prior to high‐speed treadmill exercise in a balanced 3‐way cross‐over design. Blood samples were collected for determination of furosemide, lactate, hemoglobin, blood gas, and electrolyte concentrations. Heart rate and pulmonary arterial pressure were measured throughout the run and endoscopic examination and bronchoalveolar lavage (BAL) performed. Horses were assigned an EIPH score and the number of red blood cells in BAL fluid determined. Although not significantly different, endoscopic EIPH scores were lower in the 4‐hr versus the 24‐hr and saline groups. RBC counts were not significantly different between the treatment groups. Pulmonary arterial pressures were significantly increased at higher speeds; however, there were no significant differences between dose groups when controlling for speed. A small sample size and unknown bleeding history warrant a larger‐scale study.